Red cell distribution width and mortality in carotid atherosclerosis. (21st January 2016) - Wonnerth, Anna; Krychtiuk, Konstantin A.; Mayer, Florian J.; Minar, Erich; Wojta, Johann; Schillinger, Martin; Koppensteiner, Renate; Hoke, Matthias
Abstract: Background: Red cell distribution width (RDW) is associated with morbidity and mortality in chronic cardiac disease. The aim of the present study was to investigate the role of RDW as a predictor of adverse outcome in patients with carotid atherosclerosis. Materials and methods: We prospectively studied 1065 of 1286 consecutive patients with neurological asymptomatic carotid artery stenosis as assessed by duplex Doppler sonography. The study end points were all‐cause mortality and cardiovascular mortality respectively. Results: During a median follow‐up time of 6·2 years (interquartile range 5·9–6·6), corresponding to 5551 overall person‐years, 275 patients (25·8%) died. Of them, 182 patients (66·2%) died due to cardiovascular causes. RDW was significantly associated with adverse outcome. In a continuous multivariate Cox regression analysis, the adjusted hazard ratio for each per cent increase in RDW was 1·39 (95% CI 1·27–1·53; P  < 0·001) for all‐cause and 1·43 (95% CI 1·28–1·60; P  < 0·001) for cardiovascular mortality respectively. Kaplan–Meier estimates showed a gradual relationship between increasing quartiles of RDW and death (log rank P  < 0·001). Adjusted hazard ratios for all‐cause death ranged from 0·89 to 1·94 for the highest vs. the lowest quartile ( P  < 0·001 for trend) and for cardiovascular death from 1·08 to 2·34 for the highest vs. the lowest quartile ( P  < 0·001 for trend) respectively. Conclusions: Red cell distribution width was significantly and independently associated with all‐cause and cardiovascular death in patients with asymptomatic carotid atherosclerosis.